2001
DOI: 10.1021/ja003436n
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effects on Charge Transfer Bands of Nitrogen-Centered Intervalence Compounds

Abstract: Electron transfer parameters are extracted from the optical spectra of intervalence bis(hydrazine) radical cations. Compounds with 2-tert-butyl-3-phenyl-2,3-diazabicyclo[2.2.2]octyl-containing charge-bearing units that are doubly linked by 4-sigma-bond and by 6-sigma-bond saturated bridges are compared with ones having tert-butylisopropyl- and diphenyl-substituted charge bearing units and others having the aromatic units functioning as the bridge. Solvent effect studies show that the optical transition energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
160
0
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(174 citation statements)
references
References 50 publications
7
160
0
7
Order By: Relevance
“…The optical ET is associated with the so-called intervalence charge transfer (IV-CT) band which usually appears in the NIR. Among the various issues that have been investigated are the distance dependence of ET, the influence of local bridge states (electron rich vs. electron-deficient), 7,8 temperature, 20,21 solvent 22,23 and counter ion influences 24 etc. A major aspect in MV systems concerns the shape of the ground and excited state potentials.…”
Section: Introductionmentioning
confidence: 99%
“…The optical ET is associated with the so-called intervalence charge transfer (IV-CT) band which usually appears in the NIR. Among the various issues that have been investigated are the distance dependence of ET, the influence of local bridge states (electron rich vs. electron-deficient), 7,8 temperature, 20,21 solvent 22,23 and counter ion influences 24 etc. A major aspect in MV systems concerns the shape of the ground and excited state potentials.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Leider wird die Anwendung dieser Methode bei geladenen Verbindungen durch die im elektrischen Feld auftretende Ionenwanderung, die nur durch die Verwendung von Glas-Matrices verhindert werden kann, erschwert. [11][12][13] Weitere Nachteile geladener MV-Verbindungen sind ihre geringe Löslichkeit, besonders in unpolaren Solventien, [14][15][16] sowie das Auftreten von Ionenpaareffekten. [17,18] Neutrale MV-Verbindungen, eine Verbindungsklasse, die nach unserem Kenntnisstand [19] bisher noch nicht beschrieben wurde, weisen keinen dieser Nachteile auf.…”
unclassified
“…51 The values obtained in this manner are λ v ) 10 100 cm -1 (28.9 kcal/mol) and λ s (CH 3 CN) ) 4000 cm -1 (11.5 kcal/mol), that is, the present resonance Raman . Figure 1.…”
Section: Resultsmentioning
confidence: 78%
“…These calculations were done using the partitioning of the room temperature IV band maximum in acetonitrile, taken as λ, into λ v ) 10 110 cm -1 and λ s ) 4020 cm -1 that arose from how λ changes with solvent. 51 However, other calculations showed that the results were indistinguishable if λ was not broken into vibrational and solvent components but taken as a single 14 130 cm -1 quantity (see Supporting Information). This result is very different from that obtained using Bixon-Jortner theory to calculate rate constants, where S ) λ v /ω v is a parameter of fundamental importance, so the partitioning of λ is crucial.…”
Section: I(ω)mentioning
confidence: 99%